Antimicrobial and Antioxidant Activities of Some Plant Extracts - Scio, Elita; Mendes, Renata F.; Motta, Erick V.S.; Bellozi, Paula M.Q.; Aragão, Danielle M.O.; Mello, Josiane; Fabri, Rodrigo L.; Moreira, Jussara R.; Assis, Isabel V.L. de; Bouzada, Maria Lúcia M. (IntechOpen, 2012)
None